The efficacy of ribavirin in Crimean-Congo hemorrhagic fever-randomized trials are urgently needed - Ceylan, Bahadır; Turhan, Vedat (Elsevier, 2014)
The only antiviral drug used today in Crimean-Congo hemorrhagic fever (CCHF) is ribavirin; however, its efficacy is controversial due to the lack of randomized controlled trials. The studies examining the efficacy of ribavirin in CCHF have generally been retrospective studies including insufficient numbers of patients, resulting in low power. We think that ribavirin should not be used in CCHF until randomized controlled studies have been conducted, and that only supportive treatment should be used.
WOS: 000348023600065
PubMed ID: 25461235
Keywords: Crimean-Congo; Hemorrhagic Fever-Randomized Trials